Shaping governance through social media: a review of Chinese government strategies and public engagement (2013-2023) - Chi, Jinglin; Kamarudin, Syafila; Abdul Rahman, Saiful Nujaimi (Arts and Science Press Pte. Ltd., 2024)
This systematic literature review employs the PRISMA framework to assess the literature of Chinese government social media (GSM) from 2013 to 2023. Utilizing a mixed-methods approach that combines bibliometric andcontent analysis, this review investigates the evolving use of GSM in China. The bibliometric analysis reveals significant trends in research focus and methodologies over the decade, indicating a shift towards more qualitative and mixed-method approaches as the complexity of digital governance increases. Content analysis further delineates these findings into specific themes: governance strategies and implementation, technological evolution, and the audience. Through the examination of these themes, the review highlights how Chinese GSM has been strategically used to foster a more transparent and engaging government presence online, facilitating improved public services and citizen involvement in governmental processes. This study also incorporates a brief cross-analysis to explore the interactions between different research dimensions, offering nuanced insights into the dynamics of GSM applications. This research underscores the critical role of social media in shaping modern governance, suggesting that ongoing technological adaptation and strategic communication are essential for enhancing public engagement and trust in the context of China. The findings advocate for continued research and policy development to leverage the potential of GSMfully, ensuring that digital governance strategies remain responsive to technological advancements and evolving public expectations. Keywords: government social media; China, PRISMA; bibliometric analysis; content analysis.